Cancer Care Decision Making in Multidisciplinary Meetings. (March 2015) - Dew, Kevin; Stubbe, Maria; Signal, Louise; Stairmand, Jeannine; Dennett, Elizabeth; Koea, Jonathan; Simpson, Andrew; Sarfati, Diana; Cunningham, Chris; Batten, Lesley; Ellison-Loschmann, Lis; Barton, Josh; et al.
Little research has been undertaken on the actual decision-making processes in cancer care multidisciplinary meetings (MDMs). This article was based on a qualitative observational study of two regional cancer treatment centers in New Zealand. We audiorecorded 10 meetings in which 106 patient cases were discussed. Members of the meetings categorized cases in varying ways, drew on a range of sources of authority, expressed different value positions, and utilized a variety of strategies to justify their actions. An important dimension of authority was encountered authority—the authority a clinician has because of meeting the patient. The MDM chairperson can play an important role in making explicit the sources of authority being drawn on and the value positions of members to provide more clarity to the decision-making process. Attending to issues of process, authority, and values in MDMs has the potential to improve cancer care decision making and ultimately, health outcomes.